Tuning The CuO Catalyst Properties for an Optimal H2:CO Ratio - Daniele Giusi; Angela M. Ronsisvalle; Veronica Costantino; Viviana Amoroso Sefora; Isabella Perricone; Francesco Tavella; Chiara Genovese; Claudio Ampelli (Chemical Engineering Transactions, 2025)
This study reports the design and engineering of CuO-based electrocatalysts synthesized via a facile hydrothermal approach to optimize the H2:CO syngas ratio in CO2 electrocatalytic reduction. This process offers a sustainable alternative to traditional methods by operating under mild conditions, reducing greenhouse gas emissions, and enabling the use of renewable energy. Three CuO-based electrocatalysts, synthesized by the same hydrothermal method but with different precursors, were used to prepare innovative gas-diffusion electrodes and tested in an optimized compact electrochemical flow-by reactor. Unlike conventional devices with liquid anode and cathode compartments separated by a membrane, this reactor features an additional gas chamber adjacent to the cathode liquid compartment, forming a triple gas/solid/liquid interface that enhances the local CO2 concentration at the electrode surface. The study demonstrates that introducing different salts (e.g., Li? or Na?) during synthesis enables significant modifications to the structural properties of the CuO catalysts, leading to different product distributions in CO2 electroreduction. The optimal H2:CO ratio, suitable for Fischer-Tropsch or methanol synthesis, can be modulated introducing Li+ or of Na+ salt in the synthetic CuO route, as well as by fine-tuning the operating conditions, such as the cell potential and current density. The performance differences among the catalysts were elucidated through electrochemical characterizations, including measurements of capacitance, resistance and electrochemical active area (ECSA), as well as through the analysis of hydrophilicity properties of the electrode surface.